Antineutrophil Cytoplasmic Antibody-Associated Vasculitis With Acute Kidney Injury: Short-Term Recovery Predicts Long-Term Outcome - Huang, Xiaohan; Chen, Liangliang; Lan, Lan; Ren, Pingping; Ni, Anqi; Ma, Yanhong; Wang, Yaomin; Zhu, Yilin; Xu, Ying; Chen, Jianghua; Han, Fei (Frontiers in Immunology, 2021)
Background： Kidney involvement is common in antineutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV). It tends to be aggressive, and in some patients, the kidney involvement may reach the criteria of acute kidney injury (AKI). Here, we aim to describe the clinical characteristics of these patients and find risk factors for poor outcomes. Methods： Patients diagnosed with AAV in our hospital from February 2003 to February 2017 were included. Those who reached the KDIGO AKI criteria were reclassified according to the KDIGO AKI stage. The clinical features of these patients were analyzed. Also, according to the variation of serum creatinine 3 months after AKI episode, patients were further divided into 2 groups, patients whose Scr level at the third month decreased by 30% or more from the peak Scr level was classified into G1, and others were classified into G2. Long-term renal and survival outcomes of these patients were analyzed with cox model. The renal endpoint was reaching end-stage renal disease (ESRD), and the survival endpoint was death. Nomograms were built based on cox models. Results： Of 141 AAV patients included, during the median follow-up period of 64.0 (IQR 34.8, 85.4) months, 36(25.5%) patients reached renal endpoints, and 22 (15.6%) patients died. The median renal survival time was 35.9 (IQR 21.3, 72.6) months and the median survival time was 48.4 (IQR 26.8, 82.8) months. Multivariate analysis showed that poor recovery of serum creatinine (Scr) level at 90 days (P<0.001, RR=6.1569, 95%CI 2.920-12.977), BVAS score (P=0.025, RR=1.099, 95%CI1.012-1.193), and AKI stage 3(P=0.019, RR=2.892, 95%CI1.194-7.007) were independent risk factors for renal endpoints; poor recovery of Scr level at 90 days (P=0.013, RR=2.728, 95%CI 1.126-6.613), BVAS score (P=0.015, RR=1.159, 95%CI 1.029-1.306) and age(P=0.014, RR=1.048, 95%CI 1.010-1.087) were independent risk factors for all-cause death. The c-index of nomograms is 0.830 for renal outcome and 0.763 for survival outcome. Conclusion： KDIGO AKI stage 3 is the risk factor for ESRD in AAV patients with AKI. The BVAS score and level of kidney function recovery at 90 days are the independent risk factors for both ESRD and all-cause death, and is of predictive value for outcome.